(NrOS)QÆJSXKO(B-(NUKRAÇNSXKIJ SLOWNIK (B/s)E - )Qæ(NWANICXKIJ(B, (Ns(B.,s)E; (N{UMLQNSXKIJ(B, (Nf(B.s ((NkI)QÇW (B:s)E (NoBEREGI(B,s, 2006)
(Nu SLOWNIKU PODANO BLIZXKO (B35 000 (NSL)QÆW(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NmOWOZNAWSTWOs -- (NrOS)QÆJSXKA MOWAs)E -- (NuKRA)QÇNSXKA MOWAs)E; (NSLOWNIKs; (NUKRA)QÇNSXKA MOWAs)E; (NROS)QÆJSXKA MOWAs)E